2009
DOI: 10.1007/s11882-009-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenoids and adenoiditis in children with allergy and otitis media

Abstract: Adenoids and/or tonsil inflammation with concomitant obstructive hypertrophy is one of the oldest and most common pediatric problems. Adenoids are a component of Waldeyer's ring and because of their anatomic position can be relevant in the pathogenesis of otitis media when they are inflamed and/or enlarged. Adenoid pads can create mechanical eustachian tube obstruction. Therefore, in some cases, adenoidectomy may have a role in the clinical management of otitis media with effusion. However, eustachian tube dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 31 publications
1
35
0
5
Order By: Relevance
“…6 The peak age incidence for middle ear effusions correspond to the period of maximum lymphoid hyperplasia in the nasopharynx. 8 In present study it was observed that male children were having more incidence of OME than female children. Male sex, aboriginal status, lack of breastfeeding, older siblings, daycare, passive smoke exposure and low socioeconomic status have consistently been identified as risk factors for OME.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…6 The peak age incidence for middle ear effusions correspond to the period of maximum lymphoid hyperplasia in the nasopharynx. 8 In present study it was observed that male children were having more incidence of OME than female children. Male sex, aboriginal status, lack of breastfeeding, older siblings, daycare, passive smoke exposure and low socioeconomic status have consistently been identified as risk factors for OME.…”
Section: Discussionmentioning
confidence: 48%
“…Eustachian tube dysfunction leads to negative pressure inside middle ear causing accumulation of serous or mucoid fluid within the tympanic cavity. 8 Chronic hypertrophy of adenoids is the most common cause of Eustachian tube dysfunction in children, causing otitis media with effusion. Adenoid hypertrophy can produce Eustachian tube obstruction in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…У процесі формування частих повторних запаль-них захворювань носоглотки збільшене інфекційне навантаження може сприяти гіперплазії аденоїдної тканини з формуванням механічних перешкод для нормального відтоку секрету із середнього вуха та придаткових пазух носа (із розвитком хронічних отитів, риносинуситів) [9]. Будучи одночасно ін-дуктивним і ефекторним органом захисту слизових оболонок, а також елементом уродженого й адап-тивного імунітету, аденоїди відіграють важливу роль у забезпеченні функціонування імунної системи ор-ганів дихання.…”
Section: дослідження є фрагментом науково-дослідної роботи кафедри пеunclassified
“…Exclusion criteria were as follows: an inability to perform eNO SB or eNO TB ; allergic asthma or chronic airway diseases (25); acute respiratory infections during the previous 30 d and/or the administration of systemic antibiotics and/or steroids or other medications affecting the airways (e.g., inhaled steroids, nasal steroids, or decongestants) during the previous month; systemic diseases (e.g., cystic fibrosis, primary ciliary dyskinesia, and primary or secondary immunodeficiency) (21); and parental refusal to participate.…”
Section: Patients and Settingmentioning
confidence: 99%